The effect of thematic learning by using a scientific approach to increase the multiple intelligence of students - Ririn Andriani Kumala Dewi; Piyantina Rukmini (Jurnal Prima Edukasia, 2019)
This study aims to increase the multiple intelligence of students of elementary school teacher education STKIP NU Indramayu by using thematic learning with a scientific approach and to find out the obstacles experienced by students in increasing multiple intelligence. The method used is a mix method with sequential explanatory strategy, a strategy is applied by collecting and analyzing quantitative data in the first stage, in this study data collection and analysis of multiple intelligence enhancements, followed by qualitative data collection and analysis in the second stage, obstacles students in developing multiple intelligences built based on quantitative initial results. The subjects were students of PGSD STKIP NU Indramayu who attended the basic science concepts course. The instruments used in the form of tests and interviews. The results showed an increase in multiple intelligence students after scientific approached thematic learning seen from the results of the N-gain test analysis increased by 0.41 in the medium category. Obstacles in increasing multiple intelligence students are 3, students have difficulty in analyzing existing data from the results of the study, students have difficulty in working on calculation problems, and students have difficulty in predicting a problem.